A complicated intrathecal baclofen pump implantation in a child with spastic Diplegia: Should a genetic mimic of cerebral palsy be Considered? - Mohamed Ashraf; Peter Emad Khalil; Omnia Fathy ElRashidi; Jacob Edwar Ibrahem; Hedayat Khaled Mansour; Ahmed Wael Ibrahim; Mohamed Ismael Ali; Hesham Nafea; Mostafa G. Mahran; Abdelwahab Marzouk; Walid Abdel Ghany (Interdisciplinary Neurosurgery)
Background: Management of hypertonia in children with cerebral palsy was challenged over decades including physical rehabilitation, splinting, orthopedic procedures, Botulinum toxin injection, ablative neurosurgical techniques and neuromodulation procedures including intrathecal baclofen infusion. Neurological decline is not a common fate of the classic cerebral palsy (perinatal insult). Observations: We report a 14-year-old boy child with spastic cerebral palsy diplegia showing rapid decline of neurological status following intrathecal baclofen pump implantation. The whole exome genetic sequencing of the child showed an ultra-rare bi-allelic mutation in the NFU1 gene. This gene mutation has a wide spectrum of symptoms including fatal leukoencephalopathy, muscular hypotonia, psychomotor regression, swallowing difficulties and pulmonary hypertension. Lessons: Genetic mimics of cerebral palsy may be overlooked and must be put into consideration before making surgical decisions.Previous presentations:: An abstract was accepted for oral presentation in the Ain shams Neurosurgery Congress (ASNS) in Cairo, Egypt in May 2023. There are no other presentations or submissions of publications for this case.